Coenzyme Q10 protects keratinocytes against oxidation-induced energy stress as revealed by spatiotemporal analysis of cell energetics - Roland Abi Nahed; Ali Hussein; Cécile Cottet-Rousselle; Alexandra Vogelsang; Francesco Aulicino; Imre Berger; Thomas Blatt; Julia M. Weise; Uwe Schlattner (Scientific Reports)
Abstract Coenzyme Q10 (Q10) plays a critical role in cellular energy conversion within the mitochondrial respiratory chain and offers protective effects against oxidative and metabolic stress. In this study, we investigated the impact of Q10 on the spatio-temporal patterns of cellular energetics in keratinocyte-derived HaCaT cells, utilizing the genetically-encoded FRET sensor AMPfret. Engineered from the AMP-activated protein kinase (AMPK), this sensor leverages endogenous affinities of the kinase that evolved to detect energy stress, specifically decreases in ATP/ADP and ATP/AMP ratios that pose a threat to cell survival. We successfully established HaCaT cells stably expressing AMPfret, validated their functionality by inducing energy stress with 2-deoxy-D-glucose, and demonstrated that Q10, together with high glucose conditions in culture, can enhance cellular energetics compared to low glucose controls. We then employed AMPfret to analyze the spatio-temporal response of HaCaT keratinocytes to Luperox (tert-butyl peroxide), a potent organic prooxidant, in the presence of varying intracellular levels of Q10. Preloading cells with Q10 was protective, slowing the speed and reducing the extend of the energy stress response. In contrast, preincubation with Simvastatin, an inhibitor of the mevalonate Q10 biosynthesis pathway, depleted cellular Q10 levels, accelerated the onset of energy stress, and led to early cell death as compared to controls. Under all conditions, AMPfret revealed cell-to-cell heterogeneity in energy stress at baseline and in the response to Luperox. Overall, tracking changes in energy state in time and at single-cell level allows further insights into the beneficial role of Q10 in enhancing cellular bioenergetics in skin cells, and a potential role of AMPK in mediating responses to altered Q10 levels.